Editorial - Souza, Leonardo da Rocha de; Pena, Layra Linda Rego; Silva, Cássia Katarine Sant’Anna da; Peter, Clarice Aparecida Sopelsa; Mette, Stéphanie Luíse Pagel Scharf (Revista Jurídica (FURB), 2024)
Editorial